(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
Modern food industry is characterized by increased demand for sauce products with controlled rheological properties and stable consumer characteristics. Modified starches as functional ingredients open new opportunities for creating innovative milk and cream sauces, which determines the relevance of studying their technological potential. The aim of the work was to investigate the influence of modified starches on the formation of rheological properties and structural-mechanical characteristics of milk and cream sauces, and to determine optimal technological parameters for their production. Rheological methods were used to determine viscosity characteristics of starch dispersions, microscopic studies to evaluate the structure of starch granules under different technological processing regimes, as well as organoleptic analysis of textural properties of the obtained systems. It was established that modified starches are effective structure-forming agents for creating stable milk and cream sauces with controlled rheological properties. The non-Newtonian nature of starch dispersions was experimentally confirmed, with viscosity depending on shear rate and modified starch concentration. It was found that with increasing starch concentration, the system viscosity increases significantly, allowing regulation of sauce consistency according to technological requirements. The influence of technological factors on rheological characteristics of the systems was investigated. Prolonged thermal treatment leads to viscosity reduction, while the combination of thermal and mechanical effects decreases viscosity compared to control samples. Microscopic studies confirmed that applied technological regimes do not lead to destruction of starch granules. Thermal treatment increases the degree of granule hydration, while mechanical impact is accompanied by system aeration with preservation of structural integrity. The obtained starch dispersions are characterized by short creamy texture and light flowability at room temperature, which meets technological requirements for milk and cream sauces. Optimal concentrations of modified starches were established to achieve necessary organoleptic and structural-mechanical properties of finished products. Research results confirm the prospects of using modified starches as functional ingredients for developing innovative sauce products in the food industry. The established patterns of influence of starch concentration and technological parameters on rheological properties of systems create a scientific basis for optimizing the production technology of milk and cream sauces with predictable consumer characteristics. The obtained results can be used by food industry enterprises for developing production technologies of milk and cream sauces using modified starches, which will ensure creation of products with controlled quality indicators and increased stability during storage.